FULFILLING THE RIGHTS OF CHILD VICTIMS OF SEXUAL VIOLENCE IN THE CRIMINAL JUSTICE SYSTEM IN INDONESIA - Krisna, Liza Agnesta; Wilsa, Wilsa; Rachmad, Andi; Aldino, Hanri; Hayati, Vivi; Zuleha, Zuleha; Nazarova, Lola G. (UNISSULA, 2024)
Legal protection for children who are victims of sexual crimes is an essential aspect of the criminal justice system. This research examines the concept of legal protection for child victims of sexual crimes in Indonesia, focusing on both positive and progressive legal aspects. The study aims to understand the implementation of legal protection concepts for child victims of sexual crimes within the framework of positive law, as well as to explore the impact and effectiveness of progressive law in the same context. The research methodology adopts a descriptive normative approach, utilizing both primary and secondary legal sources. Normative analysis involves identifying relevant laws and regulations, such as Law No. 13 of 2006 on Witness and Victim Protection, Law No. 11 of 2012 on Juvenile Justice System, and Law No. 12 of 2022 on Sexual Violence Crimes. Data analysis employs qualitative methods, combining literature review and field research. The findings of this research affirm that despite existing laws governing legal protection for child victims of sexual crimes, implementation remains suboptimal, with various challenges yet to be addressed. Further steps are necessary to raise awareness, strengthen law enforcement, and ensure that the rights of child victims are upheld in accordance with principles of justice and human rights.